Effect of sulcular green tea extract irrigation on experimental rabbit’s gingivitis (A histopathological study) - Baban, Dilyar A (Journal of Baghdad College of Dentistry, 2020)
Background: Considering the antioxidant, anti-inflammatory, and antimicrobial properties of green tea, this study aimed to evaluate the histopathological effect of the sulcular irrigation of green tea extract in the treatment of experimental gingivitis in rabbit. Materials and methods: For this experimental study, 45 male rabbits, separated in two groups, control non- irrigated group (5rabbits) and study group (40 rabbits), gingivitis induced by ligatures was packed subgingivally in the lower right central incisors of the experimental group for seven days. Then, the animals were randomly designated to two irrigated groups (20 rabbits for each) with 50µl/kg of distilled water and 5% green tea extract once daily for seven days starting from the day of ligature removal respectively. Specimens have taken at 1, 3, 7, and 14 days for light microscopical evaluation of inflammatory cellular infiltration. Results: Regarding study group (5% of green tea extract), results demonstrated a significant reduction in the mean values of inflammatory cell counts within three days (P≤ 0.05) to reach the amount of control group within seven days (P˃ 0.05). A highly significant difference was detected between control group and study group sprayed with distilled water during all healing periods (P≤ 0.05). Histological examination showed that the resolution of gingival inflammation, re-epithelization, and tissue healing were achieved much quicker in the group of gingival sulcular irrigation with 5% green tea extract. Conclusions: In this experimental study, the histopathological analysis demonstrated that the use of 5% extract of green tea as gingival sulcular irrigation might fasten healing after the induction of gingivitis. Keywords: green tea, animal model, gingival sulcular irrigation, experimental gingivitis.